Implementation of a Web-Based Master-Slave Architecture for Greenhouse Monitoring Systems in Grape Cultivation - Hirzen Hasfani; Uray Ristian; Wijaya, Uray Syaziman Kesuma (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2024)
The Internet of Things (IoT) technology enables electronic devices to connect to the Internet for real-time data collection and analysis. In greenhouses, IoT is used to monitor soil moisture and environmental conditions to support grape plant care. This study proposes a grape plant monitoring system using a master-slave architecture and the ESP-NOW protocol to reduce reliance on Wi-Fi networks, thus minimizing delay and packet loss. The system leverages direct communication between master and slave nodes. Testing results show an average delay of 1,546.65 ms, jitter of 120.56 ms, and packet loss of only 0.07% from 88,815 data transmissions in one day. Despite variations in packet loss due to power interruptions, the system consistently demonstrates reliable data transmission. Overall, this system proves to be reliable for real-time monitoring in greenhouses, offering stable performance and high data accuracy.